Quantification of Chlorine in solid fuels and its release behaviour during pyrolysis - Rahim, Muhammad Usman (Curtin University, 2014)
Chlorine release during biomass pyrolysis is studied in this Ph.D. project. Two novel methodsare developed for accurate quantification of chlorine in coal, biomass and plastic fuels.Pyrolysis results of sodium chloride loaded cellulose reveal that interactions betweenchlorine and cellulose organic structure cause low temperature release of HCI duringbiomass pyrolysis. Distribution of chlorine in pyrolysis products is examined under variousreactor configurations during mallee bark pyrolysis demonstrating significant non-HCIchlorine release.